(untitled) - Baskin, Yvonne (Washington, D.C, 2003)
A Plague of Rats and Rubbervines, widely published science writer Yvonne Baskin draws on extensive research to provide an engaging and authoritative overview of the problem of harmful invasive alien species
Keywords: Biological invasions,Nature conservation